The Fourth Heart Sound Revisited: Assessing Cardiographics Associated with Late Diastolic Propagating Events Using High Frame Rate Echocardiography - McCrary, Andrew W.; Moore, Cooper; Collins, Sydney D.; Sturgeon, Gregory M.; Lefevre, Melissa; Ramm, Olaf T. von; Barker, Piers C.A (Cardiology and Cardiovascular Medicine, 2025)
Background: Stroke is the second leading cause of death and the leading cause of adult disability worldwide. A better understanding of stroke risk factors and outcome may help guide efforts at reducing the community burden of stroke. Objective: To observe the relationship of hs C-Reative Protein level in first ever ischemic stroke. Methodology: This cross-sectional descriptive study was conducted in the Department of Medicine, Sir Salimullah Medical College and Mitford Hospital during the period of 6 months to find out the relationship of hs C-Reative Protein level in first ever ischemic stroke. For this purpose 100 patients with acute ischemic stroke were selected. All acute stroke patient were included as per inclusion and exclusion criteria. Then marker of stroke High Sensitivity CRP were done. Data were collected by using a preformed data sheet and statistical analysis was done in detailed and by using SPSS 20. Results: This study shows the average age was 62.12 years. Male predominance than female. CI was the most common subtype stroke (38%). The most common risk factor were hypertension (72%), then smoking (44%), hyperlipidemia (28%) and atrial fibrillation (26%). Majority (63%) were hs CRP level >3 mg/L. It was observed that hyperlipidemia and ischemic heart disease were associated with higher CRP level. Conclusion: In conclusion this study demonstrated that high CRP level is associated with stroke severity at admission and is an independent predictor of early seven-day mortality after ischemic stroke.